The Clinical Effectiveness Of Laparoscopic Appendectomy For Treating Acute Appendicitis: A Comprehensive Systematic Review - Andrea; Jesslyn (The Indonesian Journal of General Medicine, 2024)
Background: The aim of this systematic review is to comprehensively compare the clinical outcomes of laparoscopic appendectomy  and open appendectomy in the treatment of acute appendicitis. Methods: The review adhered to PRISMA 2020 standards and analyzed full-text English literature from 2014 to 2024. It excluded editorials, review papers from the same journal, and submissions lacking a DOI. Literature sources included PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of  500 articles were retrieved from online databases (PubMed, SagePub, SpringerLink and Google Scholar). After three rounds of screening, five articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: Laparoscopic appendectomy emerges as superior for acute appendicitis, with improved outcomes, fewer complications, and better resource management than open surgery. Ongoing advancements in technique and evidence will enhance surgical protocols and patient outcomes worldwide.